(untitled) (Research, Society and Development, 2022)
The National Common Curricular Base (BNCC), when dealing with the Physical Education curricular component, specifically in the gymnastics unit, points out Gymnastics for All (GFA) as an object of knowledge. With a recent change in the municipal education curriculum in Manaus, following the BNCC regulations, this practice was inserted as a Physical Education content in elementary school. Thus, this research aimed to investigate the perception of students in the early years of elementary school in a public school about GFA in physical education classes. It was qualitative research, characterized as action research. Participated in the research 16 students from a class of the 4th year of elementary school, enrolled in a municipal school in the city of Manaus. For data collection, we used a questionnaire, application of theoretical-practical classes, focus group and field diary. Data analysis was performed using content analysis. Two categories emerged from the results: “from ignorance and discomfort to satisfaction in gymnastics” and “the euphoria in the discovery of acrobatic possibilities”. It was evident that the students were unaware of the practice of GFA. In the first contact, they found the activities strange because they were used to other practices, for example, those involving the ball, but when they discovered GFA, the students showed interest, demonstrating: fun, good teamwork, creativity, interaction with colleagues and with the medium and also an interest in the plasticity of movements and figures that until then had only been seen on television, such as jumps (acrobatics) and the human pyramid.